Peran Masjid Sebagai Roda Penggerak Perekonomian Masyarakat (Penelitian Deskriptif Pada PKL di Kawasan Masjid Al-Akbar Surabaya) - Suryani, Husniyah (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this research is to find does Al-Akbar Mosque, as a place to pray for Moslems,Â as place to learn about Islam and as a tourism site influence people to do an economic activityÂ around there. The economic activity is limited at street vendors only.This research is using qualitative approach; data are collected by interview into some streetÂ vendor and by observation. After needed data collected, the data was analyzed usingÂ descriptive qualitative approach.It has summarized that there are two roles of Al-Akbar Mosque which influence people to doÂ economic activities around there. First is passive role, which Al-Akbar Mosque as a mosque, as aÂ place to learn about Islam and as a tourism site is able to attract a lot of people to come forÂ their own purposes and it motivates the street vendors to start economic activities. The secondrole is an active role, if the management of Al-Akbar Mosque didnât allow them to do so; theÂ street vendor wonât be able to sell their things there peacefully. And it is related to Al-AkbarâsÂ Mosque commitment as its function to empower ummah.